The global income gap to a healthy diet - Jonas Stehl; Lutz Depenbusch; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2023)
Access to a healthy diet is a fundamental human right, yet a significant portion of the global population faces barriers to realizing this right. Conventional poverty metrics are designed to adequately capture caloric needs but they are inadequate for capturing other essential nutritional requirements. We propose national poverty lines based on the cost of a healthy diet and explore their key metrics such as headcount ratios and the poverty gap. According to these poverty lines 2.8 billion people were poor in 2021 and US 2.546 trillion per year would be needed to lift them out of poverty. Applying specifications aligned with FAO reports these numbers rise to 3 billion people and US 2,995 trillion per year. This is in contrast to 648 million people who are considered to live in extreme poverty according to the World Bank's conventional poverty lines.
Keywords: I14; I15; I32; N30; 330; Poverty; Welfare; Healthy diets